Alcohol Abuse in Indonesia: Determinant, SWOT and CARAT Analysis - Eko Teguh Pribadi (Journal of Health Science and Prevention, 2017)
Indonesia according to the Global Health Observatory (GHO-WHO) report 2010, entered the group of countries with the lowest alcohol consumption (<2,5 liters / person / capita). It should be understood that the situasion of alcohol abuse in Indonesia is relatifly complex. The influence of local traditions as well as the lack of policies related to production, distribution, and consumption of alcohol is believed to be a time bomb. This paper aims to capture the general description of the problem of alcohol abuse in Indonesia, to analyze the determinants of the problem through 4 aspects (social, economic, cultural, and environment), to analyze the the issue through the SWOT method, as well as an opportunity to formulate remedies through CARAT approach. The method used in this paper is the descriptive analitycs through an analysis of secondary data. From the study obtained information that in the period 2008-2010 the number of alcoholic beverages are relatively fixed and not significantly changed (0.6 liters / person / capita). The national prevalence of alcohol abuse in 2007 was 4.6%, which is the highest number is the province NTT (17.7%) while the lowest is NAD (0.4%). Through SWOT analysis, strengthen policies and regulations on the production and distribution of alcoholic beverages become a strategic choice for the problem of alcohol abuse soloution. And through CARAT approach, Indonesia is expected to overcome the problem of alcohol abuse in the next 1-2 decades.